The Study of Soil Contamination by Toxocara spp. Eggs in Different Areas of Chaharmahal and Bakhtiari Province, Southwest Iran - Giti Shirvani; Rahman Abdizadeh; Koroush Manouchehri Naeini; Seifollah Mortezaei; Mina Khaksar (Shahrekord University of Medical Sciences, 2019)
Background and aims: Toxocariasis caused by the larvae of Toxocara spp. is a zoonotic infection with global distribution that is considered an important health problem in the humans. The soil is regarded as the main source of the transmission of Toxocara infection to susceptible hosts. This study investigated the existence of Toxocara spp. ova in rural and urban public areas of Chaharmahal and Bakhtiari province. Methods: A total of 180 soil samples were randomly collected from 74 public places from urban and rural areas of nine counties of Chaharmahal and Bakhtiari province during May to September, 2017. The samples were examined for Toxocara spp. eggs by the modified sucrose flotation method. Results: The contamination rate of the soil samples with Toxocara spp. ova varied within 0%-18.1% in different counties. Overall, 9 (5%) out of 180 examined soil samples were found positive for Toxocara spp. ova. Of nine investigated districts, Toxocara spp. ova were observed in four counties and the highest rate of soil contamination was found in Farsan county with 18.1%. Finally, the prevalence of Toxocara spp. eggs was more in the rural areas (6.7%) compared to the urban ones (3.3%). Conclusion: This study was the first investigation regarding the contamination of Toxocara spp. eggs in the soil of public places in rural and urban areas of Chaharmahal and Bakhtiari province. According to the results, the rate of soil contamination in this region was lower compared with the other parts of Iran. Therefore, a further study is required to determine factors that may be involved in the distribution of Toxocara spp. in different areas of this province.